The emerging roles and mechanism of m6a in breast cancer progression - Zhou, Mengying; Dong, Menglu; Yang, Xue; Gong, Jun; Liao, Xinghua; Zhang, Qi; Liu, Zeming (Frontiers in Genetics, 2022)
Breast cancer (BC) has continued to be the leading cause of cancer deaths in women, accompanied by highly molecular heterogeneity. N6-methyladenosine (m6A), a methylation that happens on adenosine N6, is the most abundant internal mRNA modification type in eukaryotic cells. Functionally, m6A methylation is a reversible modification process and is regulated by 3 enzymes with different functions, namely “writer”, “reader”, and “eraser”. Abnormal m6A modifications trigger the expression, activation, or inhibition of key signaling molecules in critical signaling pathways and the regulatory factors acting on them in BC. These m6A-related enzymes can not only be used as markers for accurate diagnosis, prediction of prognosis, and risk model construction, but also as effective targets for BC treatment. Here, we have emphasized the roles of different types of m6A-related enzymes reported in BC proliferation, invasion, and metastasis, as well as immune regulation. The comprehensive and in-depth exploration of the molecular mechanisms related to m6A will benefit in finding effective potential targets and effective stratified management of BC.